VARIASI PENGGUNAAN SUKROSA PADA MEDIUM NATA DE BANANA SKIN TERHADAP KINETIKA PERTUMBUHAN SELULOSA MIKROBIAL - Alexander Hutagaol; Fajar Restuhadi; Emma Riftyan; Edo Saputra (SAGU, 2023)
This study aims to determine the best sucrose formulation and the maximum velocity (Vmax) and Michaelis-Menten constant (KM) on the resulting microbial cellulose. This research was conducted experimentally using a completely randomized design with four treatments and four replications to obtain 16 experimental units. The treatments in this study were P1 (5% sucrose), P2 (7% sucrose), P3 (9% sucrose), and P4 (11% sucrose). The data obtained were analyzed using analysis of variance (ANOVA). If Fcount ≥ Ftable, it will be continued with the Duncan’s multiple range test (DMRT) at the 5% level. The results of variance showed that the growth kinetics of microbial cellulose biomass in the manufacture of nata de banana skin with the use of sucrose had a significant effect on the thickness of the nata, the wet weight of the nata, the dry weight of the nata, the yield and the total sugar content. The best formulation treatment for adding sucrose in this study was treatment P3 (9% sucrose), which had a thickness of 0.30 cm nata, wet weight of nata 6.18 g, dry weight of nata 0.079 g, yield 5.16%. The growth kinetics value of Nata de banana skin microbial cellulose biomass produced was the maximum speed (Vmax) of 0.96019 μM/ml and constant optimum according to Michaelis-Menten (KM) 0.61614 μM.